EFEK PERKEMBANGAN HUKUM TERHADAP MASYARAKAT (IMPLIKASI SOSIOLOGIS PERKEMBANGAN HUKUM) - Jurjani, Acep; Maryam, Eni Nuraeni (An Nawawi, 2025)
Basically, life in the world is inseparable from changes in an environment, both physical, biological, and social human environments. Social change is a variation of the accepted way of life and is caused by changes in geographical conditions, material culture, population composition, ideology or the diffusion or new discoveries in a certain society. The interaction of social change and legal change is an inseparable unit like two sides of a coin. These interactions have scientific consequences because they will be seen from a different point of view. The development of society today cannot be separated from the development of existing laws. Therefore, the law must adapt to the development of society or vice versa. When talking about changes in society and the achievement of legal goals, it means studying changes in social life that are oriented towards the process of forming laws in achieving their goals. Therefore, the object of discussion focuses on an Engineering interpretation or interpretation of changes in legal norms so that the function of law as social control and social engineering can be realized. This research discusses the development of law in society, the function of law as social engineering, and the sociological implications of the development of sharia economic law on society.